The Influence of Online Zakat Services on the Number of Muzakki at BAZNAS Makassar - Dhea Ah Hadi Pamassei; Muhammad Najib Kasim; Syahidah Rahmah (IECON: International Economics and Business Conference, 2024)
This study aims to analyze the impact of online zakat services on the number of registered muzakki at BAZNAS Makassar. The research adopts a quantitative approach using a survey method to collect data from muzakki who utilize online zakat services at BAZNAS Makassar. The obtained data is analyzed to identify the factors influencing muzakki participation in using online zakat services. The population of this study includes all muzakki registered at BAZNAS Makassar who use the online zakat service. According to BAZNAS Makassar data, there are 16,000 registered muzakki, but only about 4,000 use the online zakat service. The sample is selected using purposive sampling, which involves selecting respondents with direct experience in using online zakat services. The sample size is 200 muzakki, expected to represent the target population. Data obtained from questionnaires will be analyzed using descriptive statistical techniques to describe respondents' perceptions of the online zakat service. To examine the impact of online zakat services on the number of muzakki, simple linear regression analysis will be applied. This analysis aims to explore the relationship between independent variables (ease of access, trust in digital platforms, service fees) and the dependent variable (the number of muzakki using online services). All data analysis will be performed using SPSS (Statistical Package for the Social Sciences) software to ensure the accuracy of the results.